“Why should I?” - Anouk Broersma; Carel Jansen (Communicare)
This study aimed to discover what specific beliefs of students at a South African university should be addressed when trying to persuade them to go for HIV counselling and testing (HCT). The participants were 113 students from a previously disadvantaged university. The students completed a questionnaire that included questions about participants’ HCT intentions and about possible predictors of such intentions. Students’ HCT intention proved to be positively related to their perception of having control over their HCT behaviour (self-efficacy), and to their perception of social pressure towards going for HCT (perceived norm). The students’ belief that they would not be either too afraid or too stressed to go for HCT contributed positively to their self-efficacy, as did the belief that they would be able to deal with the possibly disadvantageous outcome of the HIV test. The students’ belief that their parents would approve of their going for HCT proved to be a strong and positive predictor of their perceived norm. Furthermore, perceived susceptibility to HIV/AIDS was positively related to HCT intention, and stigmatising attitude towards people living with HIV/AIDS (PLWHAs) was negatively related to HCT intention. These outcomes suggest that in trying to convince black students in South Africa to go for HCT, developers of promotion messages should focus on students’ susceptibility to HIV, on how to deal with the possibility that their parents might not approve of their going for HCT, and on how to cope with a possibly disadvantageous test outcome.